Can governments use Get Out The Vote letters to solve Europe's turnout crisis? Evidence from a field experiment. Issue 1 (2nd January 2018) - Bhatti, Yosef; Dahlgaard, Jens Olav; Hansen, Jonas Hedegaard; Hansen, Kasper M.
Abstract: Declining levels of turnout are a problem in European elections. Are Get Out The Vote campaigns the solution to the problem? While many studies have investigated such campaigns in the US, little is known about their effect in Europe. The article presents a field experiment in which encouragement to vote in an upcoming Danish election is delivered to more than 60, 000 first-time voters using direct personal letters. Eight different letters are designed, based on the calculus of voting and prospect theory. The sample is randomly divided into treatment groups or the control group. Using validated turnout, small positive effects of receiving a letter on turnout are found, with little difference across letters. The letters mostly mobilised voters with a low propensity to vote and thus increased equality in participation. In sum, while letters have some effect, they are not likely to be a panacea for solving Europe's turnout challenges.